2019
DOI: 10.1016/j.jphotochem.2019.111934
|View full text |Cite
|
Sign up to set email alerts
|

A revised experimental protocol for implementing the actinometry method with the Reinecke’s salt

Abstract: The present short note aims at proposing a revised experimental protocol to implement the actinometry method with Reinecke's salt. It consists in substituting, for the dosing of the thiocyanate anions produced, perchloric acid (HClO 4) by nitric acid (HNO 3), the latter being carefully chosen regarding the chemical equilibria occurring in the aqueous medium and the moderate risks of HNO 3. This substitution has been rigorously validated by carrying out the experiments in a dedicated torus batch photoreactor en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For δ = 0.025 m (i.e. in the flat torus reactor used by Rochatte et al [24] and Radjagobalou et al [29]), the ratio ζ remains close to unity, whatever the type of emission. This means that, in this case, and more generally for δ > 0.025 m, the reflection induced by the base plate can be assumed negligible.…”
Section: S7 Of the Supplementary Material)mentioning
confidence: 85%
See 2 more Smart Citations
“…For δ = 0.025 m (i.e. in the flat torus reactor used by Rochatte et al [24] and Radjagobalou et al [29]), the ratio ζ remains close to unity, whatever the type of emission. This means that, in this case, and more generally for δ > 0.025 m, the reflection induced by the base plate can be assumed negligible.…”
Section: S7 Of the Supplementary Material)mentioning
confidence: 85%
“…In this paper, the implementation of the Reinecke's salt actinometer system suitable for the visible region was proposed in a LED-driven spiral-shaped microreactor. First, the revised protocol recently developed by Radjagobalou et al [29] was successfully transferred to work under continuous-flow and with different irradiation conditions (three spectral domains, various emitted radiant powers), showing the adequacy of this method for characterizing continuous-flow microphotoreactors. Then, the experiments carried out showed that neither the length of the tubing nor the occurrence of Taylor flows with nitrogen bubbles had an influence on the photodissociation rate in the microfluidic device presented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most recent academic activities have focused on photoredox catalytical systems, the investigation of interplay between photochemistry and mass transfer, , investigation of batch and continuous operation, including oscillatory flow reactors, , and comparison of photon rate measurements using actinometry and radiometry …”
Section: Introductionmentioning
confidence: 99%
“…However, clogging of the system at high conversion, difficulty to obtain full absorption condition and the necessity to work under dimmed red light still limited its large implementation. The well‐known Reinecke salt [17–19] and meso ‐diphenylhelianthrene [20] based on respectively photoaquation and photooxidation are communally used in batch nevertheless it implies the use of toxic reactant and tedious manipulations. Another important class of visible light actinometers are thermally‐stable photochromic molecules.…”
Section: Introductionmentioning
confidence: 99%